2022
DOI: 10.1177/03063070211031192
|View full text |Cite
|
Sign up to set email alerts
|

Big N auditors and the quality of earnings: Evidence from Middle Eastern and North African countries

Abstract: In recent years, the importance of audit quality has garnered significant attention by managements, academics and the general public. In this study, we examine the relationship between Big N auditors and earnings quality in the Middle Eastern and North African (MENA) countries, where cultural and institutional contexts are quite different from those in Western countries. In addressing this issue, we employ three audit quality metrics – value relevance, abnormal accruals and earnings persistence – and use the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 117 publications
(204 reference statements)
0
3
0
Order By: Relevance
“…In the study by Al-Hiyari, Colsey, and Muqattash (2022), it is shown that, in the Middle Eastern context, auditors of the largest audit firms are not associated with audit quality, also measured by abnormal accruals, and that audit quality between large and smaller audit firms is associated with the type of clientele rather than the competence of the auditors.…”
Section: Theoretical Foundationsmentioning
confidence: 97%
“…In the study by Al-Hiyari, Colsey, and Muqattash (2022), it is shown that, in the Middle Eastern context, auditors of the largest audit firms are not associated with audit quality, also measured by abnormal accruals, and that audit quality between large and smaller audit firms is associated with the type of clientele rather than the competence of the auditors.…”
Section: Theoretical Foundationsmentioning
confidence: 97%
“…As in the present time, several corporate financial frauds have disappointed various stakeholders and attracted the attention of policy-makers and researchers to multiple domains to highlight some unobservable facts and relationships that may be useful to control managerial EM practices. Further, such financial scandals also challenged the quality and independence of the external auditor (Abu Afifa et al ., 2021; Al-Hiyari et al ., 2022; Houqe et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary high-profile (Big-4) audit firms failed to play their role sufficiently, which attracted all to their quality regarding audit work (Al-Hiyari et al ., 2022; Alzoubi, 2016; Awuye, 2022; Houqe et al ., 2017). Joint auditors (JAs) expand the reliability of financial reporting, reduce information asymmetry and lower the cost of capital (Barghathi et al ., 2020; Garcia-Blandon et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%